Integrated coastal vulnerability index for coastal flooding: A case study of the Croatian coast - Ivan Marić; Monika Peer; Anita Čipak; Kristian Kobaš; Ante Šiljeg; Nino Krvavica (Environmental and Sustainability Indicators, 2024)
The combination of accelerated urbanization and tourism-related activities, along with frequent coastal flooding, has generated pressure on the coastline of the Republic of Croatia (RH). In this paper, an integrated coastal vulnerability model (ICVI) for coastal flooding was developed. The ICVI was generated using a GIS multicriteria approach and derived from two sub-indices: the physical vulnerability index (CVIN) and the socio-economic vulnerability index (CVIS). In total, 30 criteria were used in the derivation of the ICVI, with twelve contributing to CVIS and eighteen to CVIN. The ICVI model is represented as a line divided into smaller segments, each segment indicating ICVI vulnerability levels ranging from 1 (very low) to 5 (very high). The accuracy of CVIN was evaluated using 159 geocoded coastal flood locations obtained from various websites and the official register of Hrvatske Vode flood events from 2008 to 2023. More than 80% of geocoded flood locations are situated in areas with very high (5) or high (4) CVIN. Furthermore, out of 32 settlements with officially registered flood events, 90.6% of them are located in areas with very high or high ICVI. Since all data used in the ICVI derivation were acquired from open-source databases and a user-friendly GIS-MCDA toolbox was utilized, this paper presents a cost-effective approach to modeling integrated coastal vulnerability. This model can guide decision-makers and provide them with new insights for implementing an effective integrated coastal zone management strategy.